Locus of control, supportive workplace policies and work-family conflict - Noor, Noraini M. (Psychologia Society, 2006)
The study examined the possible pathways by which locus of control influenced the relationship between workplace policies and work-family conflict. Initially, supportive workplace policies were predicted to be negatively correlated with work-family conflict. In a sample of 142 Malaysian employees combining work and family, results of the regression analyses showed that after controlling for demographic variables and locus of control, workplace policies were not related to conflict. more importantly, however, the results showed that locus of control had both direct and moderator effects on the relationship between workplace policies and work-family conflict. No mediation effect was found. The implications of these findings were discussed with respect to the literature on personality and workplace policies within the work-family linkage.